Determinants of health workers' prescription patterns for patients at primary health care facilities in Zambia - Ndhlovu, Micky (My University, 2010)
Introduction The study aimed at determining health workers’ prescription patterns using selected WHO/INRUD core drug-use indicators and investigated determinants of appropriate antibiotic prescribing in public Zambian primary health care facilities. Methods The study was a secondary data analysis of a cross sectional survey of health facility data collected in four districts of Zambia. This study extracted patients’ diagnoses and treatments and linked them to the health worker demographics and health facility characteristics in order to determine prescription patterns and factors influencing appropriate antibiotic prescribing. Results A total of 2206 prescriptions were analysed. An average of 2.5 drugs per encounter was prescribed. Injections were prescribed in 4% of the encounters. While over 95% of drugs were from the essential drug list fewer drugs were prescribed by their generic names. Only 1.5% of encounters did not result in a prescription. Antimalarial drugs and antipyretics were prescribed in at least 70% of encounters while antibiotics were prescribed in close to 40% of encounters. Of all encounters in which a systemic antibiotic was prescribed, just above a quarter were of appropriate indication and dosage. Determinants of appropriate antibiotic prescribing included patient’s age, presence of clinical wall charts and treatment guidelines; and the health worker cadre. Under-5s were more likely to receive antibiotics when indicated, though at wrong dosages. Health workers with access to guidelines were more likely to prescribe antibiotics only when indicated. Health worker cadre iv without pre-service clinical training were more likely to prescribe antibiotics when not indicated and at wrong dosages. Discussion This study showed that health workers’ performance for most of the WHO drug-use core indicators was similar to findings in other developing countries. The study also revealed overuse of antibiotics for diseases that do not require antibiotics as treatment. Increasing access to guidelines and other clinical job aids, continuous medical education for all health workers and targeted training of health worker cadres without prior medical training will contribute to better prescribing of antibiotics.
Keywords: patterns; clinics; prescriptions; Zambia